Adrenaline Injection Plus Argon Plasma Coagulation versus Adrenaline Injection Plus Hemoclips for Treating High-Risk Bleeding Peptic Ulcers: A Prospective, Randomized Trial - Seyed Alireza Taghavi; Seyed Mohammad Soleimani; Seyed Mohammad Kazem Hosseini-Asl; Ahad Eshraghian; Hajar Eghbali; Seyed Mohsen Dehghani; Bita Ahmadpour; Mehdi Saberifiroozi (Canadian Journal of Gastroenterology)
BACKGROUND/OBJECTIVE: Several combination endoscopic therapies are currently in use. The present study aimed to compare argon plasma coagulation (APC) + adrenaline injection (AI) with hemoclips + AI for the treatment of high-risk bleeding peptic ulcers.